Comparative Analysis Of Financial Performance Of Transportation And Hospitality Sector Companies Before And During The Covid-19 Pandemic - Mutia Dea Haruya; Kartini Kartini (International Journal of Social Service and Research, 2023)
This study aims to look at differences in the financial performance of companies in the transportation and hotel sectors before and during the Covid-19 pandemic in Indonesia. This research is a quantitative study using a sample of 35 companies in the transportation and hotel sector listed on the Indonesia Stock Exchange. The data used is secondary data obtained from annual reports for the period 2018-2019 before the Covid-19 pandemic and 2020-2021 when the Covid-19 pandemic occurred. The analytical method used is a differential test using the Wilcoxon Signed Rank Test on the ROA, CR, DER, and PER variables. The results of this research show that there is a significant difference in the ROA and CR variables, where the ROA and CR values before the Covid-19 pandemic were higher than during the Covid-19 pandemic, while the value of the DER variable before the Covid-19 pandemic was not lower than during the Covid-19 pandemic period and the PER value before the Covid-19 pandemic was not higher than during the Covid-19 pandemic period in Indonesia.